Green Synthesis and Characterization of Zinc Oxide Nanoparticles from Mukia maderaspatana (L.) Roem. Leaf Extract and their Antibacterial Activity - V., Catherine Sheeja; A., Anami Augustus Arul; S., Ani Besant; R., Blessy; Alexander, Hanna Jeeja (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Objective: To green synthesize and characterize zinc oxide nanoparticles from Mukia maderaspatana (L.) Roem. Leaf extract and study its antibacterial activity. Materials and Methods: The leaves of Mukia maderaspatana were collected, shade dried, powdered and leaf extract was prepared using standard procedure. Zinc oxide nanoparticles was synthesized using the leaf extract, followed by characterization studies such as UV-Vis, FT-IR and SEM were carried out. The synthesized zinc oxide nanoparticles was used for anti-microbial activity. Results and Discussion: Morphological, structural and antimicrobial properties of synthesized nanoparticles are characterized by using UV-Vis Spectrophotometer, FT-IR and SEM followed by Antimicrobial study using Disc Diffusion Method. The UV Vis spectroscopic analysis of synthesized zinc nanoparticles showed the maximum absorbance at 265.50 nm. SEM analysis shows that synthesized nanoparticles are found to be predominantly hexagonal in shape. Zinc oxide nanoparticles inhibited Escherichia coli with an inhibition zone of 16 mm. Conclusion: The study reveals an efficient, ecofriendly and simple method of green synthesis of ZnO nanoparticles using green synthetic approach.